Hospital Management Practices and Their Influence on Patient Satisfaction in Tertiary Care Facilities in Jeneponto Regency - Rahmasari; Reski, Ananda; Bakri, Ulfa (Magenta Journal De Healthymedi, 2025)
This study investigates the influence of hospital management practices on patient satisfaction in tertiary care facilities in Jeneponto Regency, Indonesia, addressing the gap in empirical evidence from developing healthcare contexts. Despite widespread acknowledgment of patient satisfaction as a vital performance indicator, limited research has systematically examined how management decisions shape patients’ experiences in decentralized healthcare systems. Using a quantitative design, the study surveyed 320 patients across tertiary hospitals, analyzing the relationship between four dimensions of hospital management service efficiency, staff responsiveness, communication quality, and facility quality and overall patient satisfaction through correlation and multiple regression techniques. The results revealed strong positive associations across all dimensions, with staff responsiveness and communication quality emerging as the most significant predictors of satisfaction. While facility quality and service efficiency contributed positively, their effects were comparatively weaker, indicating that relational and human-centered practices play a more decisive role in shaping satisfaction than structural investments. The model explained 52% of the variance in patient satisfaction, highlighting the central role of management practices in healthcare delivery outcomes. These findings carry both theoretical and practical implications: theoretically, the study extends service management scholarship by contextualizing satisfaction determinants within a developing-country healthcare system; practically, it calls for hospital leaders and policymakers to prioritize managerial strategies that enhance staff responsiveness, strengthen communication, and embed patient-centered cultures alongside infrastructure improvements. By demonstrating the managerial roots of patient satisfaction, this study contributes to a broader understanding of healthcare quality as a product of organizational choices and governance.